A new method for joining bamboo culms. (1st July 2019) - Lefevre, Benoit; West, Roger; O'Reilly, Peter; Taylor, David
Graphical abstract: Highlights: A new design for joining bamboo culms was developed. Relatively easy and cheap, therefore potentially useful in developing countries. Several design variants were investigated. The measured strength was greater than any other culm-to-culm joint for which data was available. Abstract: Bamboo culms are used extensively in load-bearing structures, especially in developing countries. There is great interest in extending their use, given that bamboo is a sustainable natural resource. However, the performance of these structures is limited by the method used to join culms together. In this paper a new design for a culm-to-culm joint is presented, based on the use of a custom-machined wooden block and metal hose-clamps. Results are presented showing the development of the design through four different clamp configurations and three different types of wood. The best design was found to have a bending strength of 88.4 MPa and a shear strength of 18.5 MPa, which are equal to or greater than the strengths of any other joint for which comparable data was available. The bending strength was approximately 70% of the maximum possible value, i.e. the bending strength of intact culms. Finite element analysis was able to predict the bending strength and failure location based on the criterion that splitting occurs at a critical value of the circumferential stress. The joint is also relatively light and, being made from readily available materials and with simple tools, it will be suitable for use in developing countries.